Meninjau Faktor Keberhasilan Implementasi Enterprise Resource Planning: Perspektif Organisasi - Akbar, Nadra Ali (E-Jurnal Akuntansi; Vol 29 No 2 (2019), 2019)
Some previous studies assess the key to successful ERP implementation is the success of the organization. The purpose of this study is to analyze and re-evaluate the factors that influence the success of ERP implementation in an organizational perspective. The design of this study used descriptive quantitative methods. The data used are primary data with questionnaires as data collection. Technical analysis of data using multiple linear regression. A total of 60 respondents were obtained from service, manufacturing and banking companies in the city of Surabaya. Based on the results of the regression analysis of organizational culture and organizational leadership has a positive and significant relationship to the success of ERP implementation. While the support of top management and organizational environment does not have a significant relationship to the success of ERP implementation. Keywords : ERP Implementation; Organization; Leadership.